Concentration of salivary cortisol and testosterone in elite women soccer players: analysis of performance in official matches (Kinesiology, 2019)
Objective: This study aims to evaluate the relation between salivary concentrations of Cortisol (C), Testosterone (T), the ratio T:C and the individual performance of top-level female soccer athletes, during official matches.Method: Eighteen female athletes from a national soccer team (23.06 ± 4.33 years old) participated in the study. Four official matches were analyzed and the match time of each player, and the index of the individual effectiveness were calculated. Players were classified in two clusters according to the individual performance (cluster 1 – the weakest individual performance; cluster 2 – the highest individual performance) using K-means and a comparison on the hormonal variables were performed.Results: The players of cluster 2 generally revealed higher values (p˂0.05) in both positive actions and individual effectiveness, when compared with the players of   cluster 1. The players of both clusters presented identical values of C, T and T:C at the four evaluated matches. The athletes of cluster 2 showed a significant increase of C (p˂0.05) and a significant decrease of T and T:C before the lost games (M2 and M5). However, there was no linear relation between the variation of both hormones during the match and the individual performance of players. Conclusion: Performance in competition revealed significant differences between players, though with no apparent relation to the hormonal kinetics of C and T before and after the matches.